PENDIDIKAN ORANG TUA DENGAN PENGETAHUAN REMAJA TENTANG PENDIDIKAN SEKS - Siti Salamah; Delfriana Ayu A (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
The situation of the rise of pornography as a misleading media to the implications of moral decadence, crime and sexual violence conducted by adolescents, is not really a new case that fills newspaper or electronic media. The purpose of this study to determine the relationship level of parents education with adolescent knowledge about sex education in State Senior High School 1 Hinai Hinai sub-district of Langkat Regency 2017. This research is analytic and using approach method by cross sectional and using primary data where population number 40 responden taken in total population. Computerized data analysis using Chi-square test through SPSS Version 13.00 shows a significant correlation between parental education level and adolescent knowledge about sex education. By comparing df = 6 <0,05, and table data X2 = 12,6. The results obtained from this reserache is It is suggested to the principal to establish cooperation with local health personnel to conduct extension activities and other activities to further enhance adolescent knowledge about sex education, it is also advisable for all school staff to be more able to conduct counseling activities for teenagers as the main media for teenagers to obtain information about correct and appropriate sex education other than parents and it is advisable to adolescents to keep improving their education and knowledge even though adolescents do more activities both at home and outside school.Keywords : Relationships, Youth Knowledge, Sex Education